2004
DOI: 10.1177/1359104504043920
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Study of Rumination and Depression in Early Adolescence

Abstract: In this study, rumination, depression, and gender role were measured in a group of fourth through sixth graders once each year for 3 years. Results supported the primary hypothesis that rumination level would best predict level of depression at each subsequent assessment. No differences were observed between genders on depression or rumination. However, masculineand femniniiie-identified adolescents had higher depression scores than androgynous individuals, and feminineidentified adolescents had the highest ru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

19
91
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(110 citation statements)
references
References 49 publications
19
91
0
Order By: Relevance
“…A number of studies have found that girls ruminate more than do boys (Broderick, 1998;Grant & Compas, 1995;Hart & Thompson, 1996;Schwartz & Koenig, 1996;Ziegert & Kistner, 2002), but a subset of those studies failed to support the hypothesis that such differences would account for gender differences in depressive symptoms (e.g., Grant & Compas, 1995;Schwartz & Koenig, 1996). In addition, several studies have not found gender differences in rumination among children and adolescents (Abela et al, 2004;Broderick & Korteland, 2004). Because we distinguish between maladaptive and adaptive forms of self-focus and in light of previous mixed results, we offer no specific prediction concerning gender differences.…”
Section: Subtypes Of Rumination Inmentioning
confidence: 99%
“…A number of studies have found that girls ruminate more than do boys (Broderick, 1998;Grant & Compas, 1995;Hart & Thompson, 1996;Schwartz & Koenig, 1996;Ziegert & Kistner, 2002), but a subset of those studies failed to support the hypothesis that such differences would account for gender differences in depressive symptoms (e.g., Grant & Compas, 1995;Schwartz & Koenig, 1996). In addition, several studies have not found gender differences in rumination among children and adolescents (Abela et al, 2004;Broderick & Korteland, 2004). Because we distinguish between maladaptive and adaptive forms of self-focus and in light of previous mixed results, we offer no specific prediction concerning gender differences.…”
Section: Subtypes Of Rumination Inmentioning
confidence: 99%
“…This coping mechanism is considered maladaptive as it involves passive fixation on negative thoughts and events with no attempt at resolution [2][3][4][5] . Rumination is associated with increased risk of developing depression 1,[6][7][8][9] and increased length and severity of depressive episodes 10 .…”
Section: Introductionmentioning
confidence: 99%
“…These differences in rumination are speculated [23] to be a result of greater pressure on girls in early childhood to yield and take the other's perspective in times of conflict and to be more other-directed. Mor and Winquist posit that this pressure to put others before the self can potentially lead to a hyper-focus on the lives and problems of others which can translate at a metacognitive level to a hyper-focus on her own problems [20].…”
Section: Introductionmentioning
confidence: 99%
“…Mor and Winquist posit that this pressure to put others before the self can potentially lead to a hyper-focus on the lives and problems of others which can translate at a metacognitive level to a hyper-focus on her own problems [20]. This increased attention on girls is also, in large part, due to the fact that girls after puberty are twice as likely to experience depression, a fact which has left depression and it's determinants in adolescent boys under-studied and under-served [13,23].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation